Syphilis incidence in Russian Federation in 2004-2013 - A. A. Kubanova; L. E. Melekhina; A. A. Kubanov; E. V. Bogdanova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The article provides analysis of changes and structure of syphilis incidence in 2004-2013 in Russian Federation.